2011
DOI: 10.1021/es200619j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Capture by Functionalized Solid Amine Sorbents with Simulated Flue Gas Conditions

Abstract: A novel solid amine sorbent was prepared using KIT-6-type mesoporous silica modified with tetraethylenepentamine (TEPA). Its adsorption behavior toward CO(2) from simulated flue gases is investigated using an adsorption column. The adsorption capacities at temperatures of 303, 313, 333, 343, and 353 K are 2.10, 2.29, 2.58, 2.85, and 2.71 mmol g(-1), respectively. Experimental adsorption isotherms were obtained, and the average isosteric heat of adsorption was 43.8 kJ/mol. The adsorption capacity increases to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 36 publications
6
99
0
Order By: Relevance
“…One appeared at 479 K indicative of PEI desorption from 45PEI@ZIF-8, and the other two peaks appeared separately at about 770 and 820 K, indicating the decomposition of ZIF-8. The TG and DTG analyses above suggested that the PEI@ZIF-8 is thermally stable until 450 K, and it has more superior stability than many other PEI modified materials, such as PEI@KIT-6 [34] and PEI@HP-20 [35], which made it a robust adsorbent for industrial applications below 450 K. Fig. 4 presents the XRD patterns of ZIF-8 and PEI@ZIF-8 with different PEI loading, which were essentially identical.…”
Section: Computational Methodologymentioning
confidence: 98%
“…One appeared at 479 K indicative of PEI desorption from 45PEI@ZIF-8, and the other two peaks appeared separately at about 770 and 820 K, indicating the decomposition of ZIF-8. The TG and DTG analyses above suggested that the PEI@ZIF-8 is thermally stable until 450 K, and it has more superior stability than many other PEI modified materials, such as PEI@KIT-6 [34] and PEI@HP-20 [35], which made it a robust adsorbent for industrial applications below 450 K. Fig. 4 presents the XRD patterns of ZIF-8 and PEI@ZIF-8 with different PEI loading, which were essentially identical.…”
Section: Computational Methodologymentioning
confidence: 98%
“…Detailed protocols of the preparation were described in our previous study. 7 The experiment for CO 2 adsorption was carried out following a procedure reported by Liu et al 9 Adsorbents were treated under a nitrogen flow at 423 K for 90 min and then cooled to the test temperature. The flow was then switched to a desired simulated flue gas.…”
Section: Methodsmentioning
confidence: 99%
“…Post combustion CO 2 capture, as a CO 2 reduction technology that could be retrofitted onto existing large CO 2 emission sources such as coal and gas-fired power plants, has been the focus of intense research in recent years [4][5][6]. In this regard, environmentally benign, efficient adsorption technologies with low parasitic power plant loads are desired as substitutes for the conventional amine solvent absorption processes traditionally considered for CO 2 Solid adsorbents have been extensively investigated as possible alternatives to amine solvents for CO 2 capture [3,4,[7][8][9][10]. Amine species supported on various solids such as silica are examples of chemisorbents that have high adsorption capacities and desirable selectivity toward CO 2 over N 2 .…”
Section: Introductionmentioning
confidence: 99%